An Assessment of Partial Edentulism in Rural Population Based on Kennedy’s Classification - Verma, Anand; Pradhan Joshi, Sarita; Maharjan, Anjana (Journal of Nepalese Prosthodontic Society, 2025)
Introduction: Oral health plays a vital role towards the quality of life. Good oral health and prevention of tooth loss improves the diet and nutritional status. An evaluation of oral condition depicts the individual’s attitude, need and the treatment facilities being provided in the community.Methods: A door to door survey in the rural population of Mathurapati VDC, Kavrepalanchok district was carried out. This community based cross-sectional study aimed to evaluate the features of partial edentulism in the age group 35-64 years in a rural population based on the Kennedy’s classification.Results: There was no statistically significant difference in the prevalence of different classes (based on Kennedy’s classification) between males and females when upper jaw was considered. In case of lower jaw, the proportion of class I and class II Kennedy’s classes were significantly higher in females. The proportion of class III subjects was higher in males.Conclusion: There is no significant correlation between sex and partial edentulism. Kennedy’s class III is the most common class of partial edentulism in the age group of 35 to 64 years. Mandibular partial edentulism is more common than maxillary partial edentulism.